2009
DOI: 10.1007/s11156-009-0112-4
|View full text |Cite
|
Sign up to set email alerts
|

Value-relevance of pension transition adjustments and other comprehensive income components in the adoption year of SFAS No. 158

Abstract: SFAS No. 158, Pension transition adjustments, OCI components, Earnings measures, Stockholders’ equity, Stock returns, Valuation implication, M40, M41,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 24 publications
4
22
0
Order By: Relevance
“…Finally, in order to identify which comprehensive income components are more value relevant, we have broken down the total comprehensive income into its components (as stated by IAS 1). The PRM is modified to include the new independent variables (as Mitra and Hossain, 2009;Kanagaretnam et al, 2009;Ernstberger, 2008;Goncharov and Hodgson, 2008) and it is specified as follows (comprehensive price regression model -CPRM): Table 3 reports descriptive statistics for the variables included in the regression models. A two-group means comparison test (t-test) has been run to assess whether the differences among country means are significant.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, in order to identify which comprehensive income components are more value relevant, we have broken down the total comprehensive income into its components (as stated by IAS 1). The PRM is modified to include the new independent variables (as Mitra and Hossain, 2009;Kanagaretnam et al, 2009;Ernstberger, 2008;Goncharov and Hodgson, 2008) and it is specified as follows (comprehensive price regression model -CPRM): Table 3 reports descriptive statistics for the variables included in the regression models. A two-group means comparison test (t-test) has been run to assess whether the differences among country means are significant.…”
Section: Methodsmentioning
confidence: 99%
“…In a market-based study, Pronobis and Zülch (2012) found that actuarial gains and losses have no value relevance, but merely add noise for the prediction of subsequent period's net income and CI. Although their study does not directly relate to actuarial gains and losses, Mitra and Hossain (2009) conversely found value relevance for the pension transition adjustments in the initial adoption year of SFAS 158 Employers' Accounting for Defined Benefit Pension and Other Postretirement Plans. They documented the stock market's negative reaction to the adverse impact of pension transition adjustments (recorded in accumulated CI) on net worth and future cash flows.…”
Section: Actuarial Gains and Losses As An Oci Itemmentioning
confidence: 90%
“…Pinto (2005) and Bae et al (2008) also report that foreign currency transaction adjustments are significantly value relevant when their parameter estimates are allowed to vary in cross-sections. Mitra and Hossain (2009) show that projected pension obligation adjustments are negatively related to stock returns and this relationship is more profound for large firms. Jones and Smith (2011) report that specific OCI item information has predictive value and is value relevant to investors' decisions.…”
Section: Literature Reviewmentioning
confidence: 95%